Present status of portfolio based training and assessment in postgraduate residency program in Bangabandhu Sheikh Mujib Medical University (BSMMU): A quantitative approach (Bangladesh Journal of Medical Education, 2022)
Since 2009, the portfolio has been a prerequisite for the evaluation of postgraduate residency programs at BSMMU. This descriptive cross-sectional study was conducted with the aim of investigating the current status of portfolio-based training and assessment in BSMMU`s postgraduate training program. Total 264 residents and 30 faculty members selected conveniently and completed the Likert scale-based questionnaire. A checklist was used for reviewing portfolios (n=33) those were preserved by residents. Study revealed that most of the respondents were male (68.6% of residents and 93.3% of faculty members). About 60% of residents have given positive views on presence of instruction and purpose about maintaining the portfolio. Several participants expressed concerns because the portfolio content is self-reported; it may include bias or inaccuracy. Regarding opinions of respondents on characteristics of portfolio, both of the respondents perceived high satisfaction on portfolio based learning, reasonable contents, and practicable and feasible use of portfolio (p